Legal Protection for Fintech Consumers Trapped in Debt Due to High Interest (Illegal Loans) - Chairus Suryati; Debi Masri; Leni Indrayani; Juliya Maria; Sattar Rasul (Outline Publisher, 2025)
The rapid development of financial technology (fintech) has increased public access to financial services, especially through online lending platforms. However, this advancement also brings significant legal challenges, particularly in consumer protection. Many individuals have become trapped in debt due to exorbitant interest rates imposed by illegal lenders operating without official licenses and often engaging in abusive collection practices. This research aims to analyze the legal protection available to fintech consumers victimized by illegal high-interest lending and to evaluate the effectiveness of existing regulations, including POJK 77/2016 and other consumer protection frameworks. The study employs a normative juridical approach with qualitative analysis of legislation, court decisions, and case studies. The findings reveal that the current legal framework is insufficient in providing both preventive and repressive protection for consumers. Weak oversight of illegal fintech operators and low financial literacy among the public are key factors behind the ineffectiveness of consumer protection. Regulatory reform, stricter law enforcement, and public education are urgently needed to ensure comprehensive protection for fintech consumers.